Sport complex booking and rental system - Wong, Di Ing (2014)
The Universiti Malaysia Pahang (UMP) Sport Complex facing problem in booking and rent sport instrument. All record are done by manual recording. This is not efficient and systematic. Another problem in booking is that every time student booking multiple court. Regarding renting instrument system, Sport Complex do not have a complete system to record who has rent the sport instrument and what sport instrument has been rented. Every time a student rent sport instrument in Sport Complex, they only need to putdown the matric card and manual record down what instrument have been rented. By using the Sport Complex Booking and Rental system, it helps staff solve daily workloads in an efficient and systematic manner. All record of booking and rental can be done just within a few clicks of button. Student need to register account before they make a booking and rental. If they do not have account, the system cannot proceed the booking and rental. So, the system will record down the history into database when booking or rental is done. Besides that, staff no need to write receipt again, the system have function to send receipt to student email. All this can makes the work become easier and faster.